2022
DOI: 10.1021/acsami.1c25072
|View full text |Cite
|
Sign up to set email alerts
|

Spiky Cascade Biocatalysts as Peroxisome-Mimics for Ultrasound-Augmented Tumor Ablation

Abstract: Ultrasound (US)-augmented tumor ablation with sono-catalysts has emerged as a promising therapeutic modality due to high tissue penetration, nonionizing performance, and low cost of US-based therapies. Developing peroxisome-mimetic cascade biocatalysts for US-augmented synergistic treatment would further effectively reduce the dependence of the microenvironment H2O2 and enhance the tumor-localized reactive oxygen species (ROS) generation. Here, we proposed and synthesized a novel spiky cascade biocatalyst as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Bioactive Au NPs are good nanozymes that exhibit intrinsic enzyme activities of catalase and peroxidase. 32 Au NPs can not only promote the charge separation and inhibit charge recombination but also change the charge distribution of UIO-66. As shown in Figure 1, UIO-66 NPs were synthesized through a hydrothermal reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioactive Au NPs are good nanozymes that exhibit intrinsic enzyme activities of catalase and peroxidase. 32 Au NPs can not only promote the charge separation and inhibit charge recombination but also change the charge distribution of UIO-66. As shown in Figure 1, UIO-66 NPs were synthesized through a hydrothermal reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a combination of UIO-66 and Au nanoparticles (UIO-66-Au NPs) as piezoelectric sonosensitizers is proposed. Bioactive Au NPs are good nanozymes that exhibit intrinsic enzyme activities of catalase and peroxidase . Au NPs can not only promote the charge separation and inhibit charge recombination but also change the charge distribution of UIO-66.…”
Section: Introductionmentioning
confidence: 99%
“…However, these small porphyrins are less chemically and biologically stable and require further optimization. A series of recent studies have found that metalloporphyrin complexes can optimize these properties 112 . For instance, Liu's group had designed a multifunctional nanoplatform (named R-S-NTP) based on Fe (III), meso-tetrakis (4-sulfonatophenyl) porphyrin (TPPS), Bis (DPA-Zn)-RGD, and manganese superoxide dismutase (SOD 2 , an important antioxidant enzyme) siRNA for enhancing the production of ROS through targeted delivery and triple regulation methods, including SOD 2 down-regulation, glutathione depletion and Fenton reaction ( Figure 4 A ).…”
Section: Cdt-based Combination Therapymentioning
confidence: 99%
“…Moreover, Yuan et al proposed and synthesized a novel doping cascade biocatalyst as a peroxisome mimetic, consisting of several enzyme mimetics, such as glucose oxidase mimics (Au nanoparticles for producing H 2 O 2 ) and heme-mimetic atomic catalytic centers (Fe-porphyrin for ROS generation). The synthesized doping cascade biocatalysts suggested that the therapeutic effect of malignant melanoma can be significantly enhanced in in vivo animal data [ 108 ].…”
Section: Cutaneous Melanomamentioning
confidence: 99%